Men in Women's Worlds Constructions of Masculinity in Women's Magazines - Coffey-Glover, Laura; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2019)
This book presents an analysis of masculinity construction in a large corpus of women's magazines, adopting a feminist Critical Stylistic approach to reveal how men are talked about and 'sold' to women as part of a successful performance of hegemonic femininity. This novel approach identifies women's magazines as sites of 'lad culture' that perpetuate ideologies more commonly associated with the 'laddism' of male-targeted media. It examines how stereotypical images of men as naturally aggressive and obsessed with sex are promoted, as well as considering some of the ways in which women's magazines contribute to the social construction of normative understandings of gender and sexuality more broadly. This engaging work will offer fresh insights to students and scholars of (Critical) Discourse Analysis, Sociolinguistics, Corpus Linguistics, Stylistics, and Gender and Communication Studies. Laura Coffey-Glover is Lecturer in Linguistics at Nottingham Trent University, UK. She has published articles on various topics relating to gender construction in the media, including as part of the Discourses of Marriage research group, and sits on the editorial board for the journal of Language and Discrimination. .
Chapter 1: Introduction: Analyzing Gender Construction in Women's Magazines -- Chapter 2: Approaches to Studying Language and Gender -- Chapter 3: Women's and Men's Magazines -- Chapter 4: Data and Method -- Chapter 5: Lads, blokes and monsters: strategies of naming and description -- Chapter 6: 'Good men' and 'bad men': equating and contrasting -- Chapter 7: Representing Processes -- Chapter 8: Implicit masculinity: Assuming and Implying -- Chapter 9: Conclusion: The Men in 'Women's Worlds'.
Keywords: Sociolinguistics; Linguistics -- Methodology; Sex; Communication; Feminism; Feminist theory; Sociolinguistics; Research Methods in Language and Linguistics; Gender Studies; Media and Communication; Feminism and Feminist Theory